THU0036 Proteome Analyses of HDL Particles Allows to Identify Biomarkers of Disease Activity in SLE Patients: Gelsolin, Indian Hedgehog Protein and S100A8. (9th June 2015) - Parra, S.; Canela, N.; de las Heras, M.; Amigό, N.; Sahun, P.; Correig, X.; Castro, A.
Abstract : Background: Several studies have highlighted the complexity and the intriguing role of HDL in different pathologic conditions beyond the atherosclerotic process, such as infections, neoplasms and autoimmune diseases.HDL particles show qualitative changes that evolve HDL lipoproteins to a "proinflammatory"- HDL that has been associated with the presence of subclinical atherosclerosis in SLE patients. Thanks to new proteomics techniques it has been discovered that HDL-associated proteins are involved in functions beyond reverse cholesterol transport and related to complement activation and systemic inflammatory response. Objectives: Identify modifications in the proteome of HDL particles in 9 SLE patients in clinical remission remission respect the control group and in a clinical outbrake Methods: Serum samples were obtained from 9 SLE patients in clinical remission and when they developed a flare, 9 healthy controls matched by age and gender were recluted for the study.High Density Lipoprotein (HDL) was obtained by serum precipitation.The supernatant apolipoprotein B-depleted serum was ultracentrifugated during 40h to purify the HDL. The quantitative proteomic analyses was performed using TMT isobaric tag labelling (MALDI-TOF MS) and nanoLC-Orbitrap (nLC-MS/MS). Statistical analyses were performed using the equipment of Servei Recursos Científics i Técnics (SRCiT) in Universitat Rovira i Virgili. Results: A total number of 140 entities (protein identification-quantification_OffGel Analyses) were identified. We applied as a filtering those proteins that appears in more than 70% of samples. After the Kruskal-Wallis test, a Principal Component Analysis (PCA) were performed and also a clustering analysis that allowed to group the samples in the three groups regarding the entities with a significant fold-change (>1.1). We found 19 proteins associated to HDL that were in a significant different cincentrations respect the SLE patients and the control group. Between them, we highlight those with well known biological functions. We found that SLE patients significantly presented a higher concentration of ApoC-III, Apo-AII, ApoD, ApoC-II, Apo-CI, ApoF and ApoM. Between lupus patients in flare stage and remission we identified 4 proteins that changed significantly. HDL from patients in clincal outbreak showed an increase of C4 complement component (humoral innate immunity), and Indian Hedgehog protein (IHH) (involved in arthritis). By the other hand, we found a decrease of a protein called gelsolin important to prevent the toxic effect of actin under circumstances of tissue damage.The other protein found in a lower concetration in HDL from SLE patients with a flare, is the S100A8 protein (component of calprotectin) Conclusions: Anlyses of the proteome cargo from HDL in SLE patients identifies differences in proteins that could explain changes in HDL functionality and in lipid metabolism. Three novel HDL -associated proteins allows to distinguish the presence of a clincal outbrake in SLE. These proteins could be used as future biomarkers of the presence of arthritis ( Indian Hedgehog ), tissue-damage ( gelsolin ) and inflammation ( (S100A8 ). Disclosure of Interest: None declared